Differences in the association of oral health knowledge, attitudes, and practices with frailty among community-dwelling older people in China - Chenglin Cao; Shengdong Liao; Wenwen Cao; Ying Guo; Zixuan Hong; Bohua Ren; Zhi Hu; Zhongliang Bai (BMC, 2023)
Abstract Background Oral health and frailty are significantly related and should be well examined, especially in late life. Few studies have explored the relationship of oral health knowledge, attitudes, and practices with frailty and examined sociodemographic variations in this association. This study aimed to examine the association between oral health knowledge, attitudes, practices and frailty, with a special focus on comparing differences in their association among the Chinese community-dwelling older population. Methods This study included 4218 community-dwelling older adults (aged ≥ 60 years) who participated in a cross-sectional survey. Sociodemographic characteristics, oral health knowledge, attitudes, practices, and frail status (non-frailty, pre-frailty, and frailty) were collected with a face-to-face questionnaire-based interview. Multivariate logistic regression models were used to evaluate the association of oral health knowledge, attitudes, and practices with frailty. Results Of the 4218 participants, 36.2% (n = 1527) and 18.8% (n = 792) were classified as pre-frailty and frailty. Age, gender and educational attainments differences existed in the association of oral health knowledge with frailty. Urban-rural differences in the association of oral health knowledge and practices with frailty were also found. Specifically, oral health knowledge was significantly related to frailty only among participants aged 70-79 years (adjusted odds ratio [95% confidence interval]) (1.08 [1.02-1.15]), females (1.05 [1.00-1.10]), rural residents (1.06 [1.01-1.12]), and those who were primary school and lower education (1.06 [1.01-1.11]), whereas oral health practices were related to frailty only among urban participants (0.96 [0.92-1.00]). Conclusion This study confirmed the different associations of oral health knowledge and practices with frailty among community-dwelling older people in China. Further research is needed to better understand the abovementioned differences and public health strategies are required to improve oral health literacy and thereby contain the development of frailty in later life.